Taxing America - Brown, Karen B., 1954-; Fellows, Mary Louise (Critical America., 1996)
In the winter of 1996, Steve Forbes--publisher, heir, and presidential candidate--captured the American imagination with his proposal for a flat tax. But while Mr. Forbes claimed that such a tax would level the economic playing field by eliminating countless loopholes and miles of red tape, his actual proposal betrayed such claims to fairness by overtaxing workers and undertaxing financial capital. In the face of recent proposals for dramatic and far-reaching tax reform, Taxing America takes a critical look at the way the federal government collects its revenue and exposes the bias at the h.